Study on the Hardware in the Loop for Power Transmission System of Electric Vehicle Equipped with Electro-mechanical Continuously Variable Transmission - Ye Ming; Dai Jun; Li Si; Gongye Xiangyu; Xia Chao (Jixie chuandong)
The configuration of electric vehicle equipped with electro-mechanical continuously variable transmission（ EMCVT） is put forward based on the analysis of work principle of EMCVT,and the simulation model of electric vehicle equipped with EMCVT is built by MATLAB/Simulink platform. The hardware in the loop system of powertrain is built by LABCAR platform and the simulation test is conducted to verify the EMCVT function of the control unit and the feasibility of control strategy. Simulation results indicate that the power performance of electric vehicle is improved by using this control strategy and the configuration is feasibility.